A Comparison of Children's Ability to Read Children's and Adults' Mental States in an Adaptation of the Reading the Mind in the Eyes Task - van der Meulen, Anna; Roerig, Simone; de Ruyter, Doret; van Lier, Pol; Krabbendam, Lydia (Frontiers in Psychology, 2017)
The ability to read mental states from subtle facial cues is an important part of Theory of Mind, which can contribute to children's daily life social functioning. Mental state reading performance is influenced by the specific interactions in which it is applied; familiarity with characteristics of these interactions (such as the person) can enhance performance. The aim of this research is to gain insight in this context effect for mental state reading in children, assessed with the Reading the Mind in the Eyes (RME) task that originally consists of pictures of adults' eyes. Because of differences between children and adults in roles, development and frequency of interaction, children are more familiar with mental state reading of other children. It can therefore be expected that children's mental state reading depends on whether this is assessed with children's or adults' eyes. A new 14 item version of the RME for children was constructed with pictures of children instead of adults (study 1). This task was used and compared to the original child RME in 6–10 year olds (N = 718, study 2) and 8–14 year olds (N = 182, study 3). Children in both groups performed better on the new RME than on the original RME. Item level findings of the new RME were in line with previous findings on the task and test re-test reliability (in a subgroup of older children, n = 95) was adequate (0.47). This suggests that the RME with children's eyes can assess children's daily life mental state reading and supplement existing ToM tasks.